Perceptions of Students About the Use of Plastination in Anatomy Lessons - Güzel, Barış Can; Baygeldı, Saıme Betül; Ozkan, Zaıt Ender (My University, 2022)
Objective: This study was to examine the opinions of first year veterinary faculty students about the use of plastinated anatomic prosections in addition to wet cadavers in anatomy practical lessons. Materials and Methods: The students were shown plastinated organs and organs fixed in formaldehyde. Then a questionnaire comprising 7 questions was administered to the 100 student participants. The questionnaire responses were analyzed statistically using SPSS vn. 22.0 Frequencies software. Results: In response to question 1, 58.4% of the students thought that there was no anatomic difference between the plastinated organs and the organs fixed in formaldehyde. In contrast to the strong smell of formaldehyde, 88% of the students stated that the plastinates were odourless. The use of plastinated organs was thought to improve the quality of education by 89.1% of the students, compared to the negative aspects of formaldehyde. It was stated by 84.2% of the students that plastinated organs should be included in anatomy lessons due to the thoughts of the majority of the students that plastinated tissues could make a greater contribution to anatomy lessons. In response to the final question, 92.1% of the students stated that they felt no abhorrence of the plastinated organs. Conclusion: Plastination may be especially useful for educational institutions without access, space, or the financial resources for dissection, and can emphasize unique or pathological samples. The results of this study demonstrated that plastinated samples were perceived as a useful addition to traditional resources in the teaching of anatomy.
Keywords: Anatomy; Questionnaire; Plastination